2017
DOI: 10.1002/adsc.201701011
|View full text |Cite|
|
Sign up to set email alerts
|

Palladium‐Catalyzed Three‐Component Tandem Reaction for One‐pot Highly Stereoselective Synthesis of (Z)‐α‐Hydroxymethyl Allylic Sulfones

Abstract: A novel method is reported for the stereoselective synthesis of highly functionalized allyl aryl sulfones. This protocol is based on a Pdcatalyzed three-component tandem reaction of sulfonyl hydrazides and aryl iodides with allenes and exhibits high (Z)-selectivity, good yields, minimal waste, ample product scope, and operational simplicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…The Scheme has shown several metal‐catalyzed regioselective additions of sulfonyl hydrazides to unsaturated bonds via formation of π‐metal‐allyl species . Allenes and in situ generated π‐allylpalladium intermediates from allylic amines were tested in this decade. Lu and co‐workers employed arylpropyne compounds as the precursor of linear allenes (Eq.…”
Section: Rso2‐[metal] Intermediatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Scheme has shown several metal‐catalyzed regioselective additions of sulfonyl hydrazides to unsaturated bonds via formation of π‐metal‐allyl species . Allenes and in situ generated π‐allylpalladium intermediates from allylic amines were tested in this decade. Lu and co‐workers employed arylpropyne compounds as the precursor of linear allenes (Eq.…”
Section: Rso2‐[metal] Intermediatesmentioning
confidence: 99%
“…52‐2). Gong and co‐workers designed a three‐component reaction for synthesis of ( Z )‐α‐hydroxymethyl allylic sulfones (Eq. 52‐3).…”
Section: Rso2‐[metal] Intermediatesmentioning
confidence: 99%
“…Remarkably, alkylvinylethylene carbonates gave the corresponding aliphatic products (41-45) as exclusively cis-isomers in good yields. This represents a complementary method to the recent elegant publication of Gong et al, [16] who reported a palladiumcatalyzed three-component tandem reaction of allenes with aryl iodides and sulfonyl hydrazides. However, using their protocol, aliphatic sulfonyl hydrazides and aliphatic iodides failed to give (Z)-allylic sulfones.…”
Section: Direct Synthesis Of Substituted (Z)-allylic Sulfones By Pallmentioning
confidence: 90%
“…Interestingly, the desired product was obtained in the presence of Pd(0) ( Table 1, entries 9 and 10). Other parameters, such as catalyst loading, ligand, atmosphere, and sodium benzenesulfinate equivalents, were also tested, with optimal conditions eventually determined (see Table 1, entry 16). Reactions conducted in DCM, CH 3 CN, toluene, and MeOH resulted in diminished yields, while using THF afforded a lower Z/E ratio (Table 1, entries 11-15).…”
Section: Direct Synthesis Of Substituted (Z)-allylic Sulfones By Pallmentioning
confidence: 99%
“…Interestingly, allene 476 lacking hydroxyl unit, failed to yield the corresponding substituted alkene 477 , supporting the proposed mechanistic pathway and the coordinative role of the OH group in the reported transformation ( Scheme 82 , reaction b). 307 309 …”
Section: Synthetic Utilitymentioning
confidence: 99%